Analisis Pengaruh Kedisiplinan Kerja Dan Kerja Sama Tim Terhadap Kinerja Karyawan PT. Raja Multi Sarana Di Makassar - Marsuki (Jurnal Online Manajemen ELPEI, 2025)
The purpose of this research is to determine (1) the influence of work discipline on employee performance at PT. Raja Multi Sarana in Makassar. (2) the influence of teamwork on employee performance at PT. Raja Multi Sarana in Makassar. (3) the influence of work discipline and teamwork simultaneously on employee performance at PT. Raja Multi Sarana in Makassar. The population in the study were employees of PT. Raja Multi Sarana in Makassar, numbering 48 people. The sample was determined using a saturated sample of 48 respondents. Research data uses primary data collected through distributing questionnaires to employees. The data analysis method in this research uses multiple linear regression analysis, coefficient of determination and t test (partial) and F test (simultaneous). The results of the analysis show that 1. Work discipline has a positive and significant effect on employee performance. 2. Teamwork has a positive and significant effect on employee performance. 3. Work discipline and teamwork simultaneously have a positive and significant effect on employee performance at PT. Raja Multi Sarana in Makassar. The large contribution of the influence of work discipline and teamwork on employee performance at PT. Raja Multi Sarana in Makassar is 72.2% while the remaining 27.8% is influenced by other variables not studied.